1967
DOI: 10.1161/01.res.21.5.741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exteriorization of the Sheep Fetus on Its Cardiovascular Function

Abstract: Exteriorized sheep or goat fetuses, with placental circulation continuing, have been extensively used for measurements of fetal cardiovascular function. However, the effects of this procedure on fetal cardiovascular function have not been assessed. We inserted vinyl catheters into an umbilical vein, an umbilical or fetal hindlimb artery, and a hindlimb vein. We measured umbilical arterial and venous blood gas tensions, umbilical blood flow using the steadystate diffusion antipyrine method, and fetal arterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 9 publications
5
29
0
Order By: Relevance
“…for prenatal carotid blood gas tensions (Pa02 = 25.3 -1 1.9 mmHg, Paco2 = 20.4 + 2.7 mmHg) and acid base status (pH = 7.29 f 0.02, HC03-= 13.3 + 4.3 mEq/liter) fell within the range previously reported in fetuses of similar gestational age (14). It has been recognized that exteriorization of the fetus leads to some differences in placental gas exchange (5). Figure 1 illustrates sequential Pao2, Paco2, pH and, rectal temperature data in lamb #50681 after exteriorization delivery, and during 165 min of liquid ventilation.…”
Section: Resultssupporting
confidence: 67%
“…for prenatal carotid blood gas tensions (Pa02 = 25.3 -1 1.9 mmHg, Paco2 = 20.4 + 2.7 mmHg) and acid base status (pH = 7.29 f 0.02, HC03-= 13.3 + 4.3 mEq/liter) fell within the range previously reported in fetuses of similar gestational age (14). It has been recognized that exteriorization of the fetus leads to some differences in placental gas exchange (5). Figure 1 illustrates sequential Pao2, Paco2, pH and, rectal temperature data in lamb #50681 after exteriorization delivery, and during 165 min of liquid ventilation.…”
Section: Resultssupporting
confidence: 67%
“…Finally, acute surgical exteriorization of the fetus is associated with a decline in umbilical flow and related parameters of ventricular function (13). Nevertheless, contractile indices obtained after exteriorization of fetuses but before simulation of birth were stable and compared favorably with those obtained in older lambs (Gps I1 to IV), suggesting that acute exteriorization did not alter these measurements of contractile state in our fetuses to any great degree.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, we considered the potential effects of anesthesia, thoracotomy, and instrumentation on neonatal ventricular function. In contrast to the marked depressant effect of barbiturates on myocardial function (13,32), alpha chloralose has been shown to induce only minimal cardiovascular depression (32). Further, in the doses utilized, alpha chloralose does not alter oxygen consumption in the newborn lamb (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing splanchnic nerve sections, Comline and Silver (4,5) have shown that sympathetic innervation of the adrenal gland is an important mediator of E release in the late gestation fetus; however, concern persists about these findings because of the acute nature of these experiments performed in exteriorized and anesthetized fepl lambs (12). Furthermore, little information exists about the response of fetal lambs in utero to hypoxemia after a more generalized reduction in sympathetic neuronal tone.…”
Section: Discussionmentioning
confidence: 99%